The Impact of ODA on domestic fiscal revenue mobilization of recipient countries - Kabanda, Emmanuel (KDI School, 2012)
ODA (Official Development Assistance) finances government expenditure is crucial in raising the living standards of the poor in the developing world. There is a debate, however, regarding the impact of ODA on recipient countries with proponents emphasizing that foreign aid, in addition to filling the government budgetary gaps of developing countries to meet their obligations to their citizenry, it increases the imperative on the recipients’ efforts to develop their own capacity with the hope that this will enable them to wean off aid; opponents argue that it stifles the capacity of recipient governments to create, support and tax their domestic sources and instead perpetuates their dependence on aid, promotes rent-seeking, corruption and civil strife. This study examines the impact of ODA on Rwanda’s efforts and capacity to generate domestic fiscal revenue and draws on the findings to reach a conclusion.
Thesis(Master) --KDI School:Master of Public Policy,2012